Undergraduate dental students and dentists' acceptability and knowledge about selective caries tissue removal - Luciana Lourenço Ribeiro Vitor; Eloá Cristina Passucci Ambrosio; Paula Karine Jorge; Natalino Lourenço Neto; Thiago Cruvinel; Maria Aparecida Andrade Moreira Machado; Thais Marchini Oliveira (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2023)
Aim: The aim of this study was to evaluate the acceptability and knowledge of undergraduate dental students and dentists on selective caries tissue removal (SCTR). Materials and Methods: Third- and fourth-year Dentistry undergraduates (Group 1) and graduates working in a Hospital Dentistry Center (Group 2) were included in the study. Participants anonymously and confidentially answered a validated questionnaire containing eleven questions on the diagnosis and management of deep caries lesions. Pearson's Chi-square test and multivariate logistic regression compared the answers (p<0.05). Results: Total sample comprised 146 participants. Of these, 81.5% were female; 52.05% were graduates and the most prevalent age group was 18-29 years old (85.62%).  Sixty-nine participants chose stepwise caries removal (p=0.027). The logistic regression analysis showed statistically significant differences. The participants who considered pulp wall moist have approximately eight times more likelihood to choose an invasive treatment (p=0.028). Those who chose endodontic treatment as an option for two-year survival have three times more likelihood to choose an invasive treatment (p=0.032). Those who affirmed that the carious dentin close to the pulp should not be removed had almost three times more likelihood to choose minimally invasive treatments (p=0.031). Discussion: Studies with questionnaires can be useful tools to detect whether the students and dentists are following the most current evidences to treat deep carious lesions. Conclusion: The participants had certain level of knowledge on SCTR, but the technique acceptability lacked consensus.